Localization and irregular distribution of Na,K-ATPase in myelin sheath from rat sciatic nerve - Alberti, Sandra; Gregorio, Elisa Aparecida; Spadella, César Tadeu [UNESP]; Cojocel, Constantin (Churchill Livingstone, 2007)
Sodium, potassium adenosine triphosphatase (Na,K-ATPase) is a membrane-bound enzyme that maintains the Na+ and K+ gradients used in the nervous system for generation and transmission of bioelectricity. Recently, its activity has also been demonstrated during nerve regeneration. The present study was undertaken to investigate the ultrastructural localization and distribution of Na,K-ATPase in peripheral nerve fibers. Small blocks of the sciatic nerves of male Wistar rats weighing 250-300g were excised, divided into two groups, and incubated with and without substrate, the para-nitrophenyl phosphate (pNPP). The material was processed for transmission electron microscopy, and the ultra-thin sections were examined in a Philips CNI 100 (TM) electron microscope. The deposits of reaction product were localized mainly on the axolemma, on axoplasmic profiles, and irregularly dispersed on the myelin sheath, but not in the unmyelinated axons. In the axonal membrane, the precipitates were regularly distributed on the cytoplasmic side. These results together with published data warrant further studies for the diagnosis and treatment of neuropathies with compromised Na,K-ATPase activity. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Na,K-ATPase; rat sciatic nerved K-pNPPase; myelin sheath